PENDAFTARAN TANAH SISTEMATIK LENGKAP MENGGUNAKAN INA-CORS BIG METODE RTK-NTRIP DI DESA LANGGINI KECAMATAN BANGKINANG KABUPATEN KAMPAR - Farouki Dinda Rassarandi; Yusra Masyur Rausanjaya; Hafidzur Rosyad Al Makhi An Nusuki (Politeknik Caltex Riau, 2021)
Complete Systematic Land Registration Program is considered to be able to produce greater results in a relatively shorter period of time, with data collection done simultaneously on all parcels of land contained in a village/district area. With the simultaneous data collection, it will be easier to reduce disputes regarding the equivalent rights of land, both fellow communities or with the government. This study uses the RTK-NTRIP and CORS methods as a base, CORS in designed as a careful reference that supports the measurement of GNSS. The correction signal is sent by CORS using the NTRIP method via the internet network to the rover station. The data obtained can be directly downloaded from the rover to the computer, the results are in the form of coordinates that have been corrected. The final results of this study is the Peta Bidang Tanah (PBT), PBT can only be made after passing through several stages and this PBT is also the most important element the Complete Systematic Land Registration. After PBT is submitted to the National Land Agency, it can only be disbursed